Designing a Territorial Composite Vulnerability Index to guide public health action in Cali, Colombia - Carlos E. Pinzón Flórez; Marcela Díaz; Luis Guillermo Echeverry; Germán Escobar Morales (PLoS ONE, 2026)
Background Social determinants of health are central to explaining health inequalities. In fragmented urban contexts such as Cali, Colombia, territorially focused public health action requires analytical tools to identify priority areas for intervention. Objective To design and apply a Territorial Composite Vulnerability Index for the city of Santiago de Cali to support the micro-planning of public health interventions. Methods We conducted an ecological, citywide study with a geospatial, multivariate approach. Seven indicators representing social determinants were selected: multidimensional poverty, critical overcrowding, youth unemployment, adult illiteracy, limited access to basic services, food insecurity, and population officially registered as victims of violence and displacement. Indicators were standardized and combined using principal component analysis to derive a single composite score. Spatial patterns were depicted with choropleth maps, and local indicators of spatial association were used to identify statistically significant clusters of high vulnerability. Construct validity was assessed by examining correlations between the index and health outcomes, including infant mortality, adolescent pregnancy, and suicide attempts. Results The composite index explained 74.3% of the joint variance of the underlying indicators. High-vulnerability areas concentrated in the eastern and hillside zones of the city, with significant high–high clusters in communes 13, 14, 15, 18, and 20. The index showed positive correlations with infant mortality, adolescent pregnancy, and suicide attempts, supporting its criterion validity. Conclusions This Territorial Composite Vulnerability Index is a valid and operational tool for guiding territorial public health management. It enables targeting of interventions to areas at greater risk and supports intersectoral and community action. Incorporating the index into local planning may help reduce social gaps in health within fragmented urban settings.